Analisis Pengalihan Kewajiban Nafkah Orang Tua Kepada Anak Di Bawah Umur Dalam Perspektif Maqasid Al-Syari'ah - Wildan, Muhammad; Maimun; Hasanah , Uswatun (Kartika: Jurnal Studi Keislaman, 2026)
This study analyzes the transfer of parental financial responsibility particularly that of the father to underage children from the perspective of Maqāṣid al-Syarī‘ah, with the research conducted in Keteguhan Village, Bandar Lampung City. Using a descriptive qualitative field research method, the study finds that the transfer of financial responsibility frequently occurs due to extreme poverty, paternal unemployment, and a lack of parental responsibility. These conditions force children aged 10–17 to work in the informal sector to support their families. In Islamic law, providing for children is an absolute obligation of the father as qawwām, encompassing physical, spiritual, educational, and health needs. The transfer of this obligation is only permissible under emergency conditions, such as when the father is severely ill, incapable, or deceased, in which case the responsibility shifts to close relatives or the state not as a means of relinquishing paternal duty. From the perspective of Maqāṣid al-Syarī‘ah, this practice contradicts the principles of protecting life (ḥifẓ al-nafs) and lineage (ḥifẓ al-nasl), as it deprives children of their fundamental rights. Therefore, stricter law enforcement, religious education, and strengthened social assistance programs are necessary